Empirical Investigation on Breakdown Characteristics of Air – CO2 Gas Mixtures Under AC and DC Voltages - Azizol, N.; Kamarudin, M. S.; Yousof, M. F. M.; Jamail, N. A. M.; Rahman, R. Abd.; Othman, N. A.; Baharom, M. N. R.; Wari, J. M. (International Journal of Engineering and Technology, 2018)
For years there have been countless efforts to find an environmental-friendly gas or gas mixtures to minimize SF6. Researchers have been ongoing to find its alternatives where there are few gasses used to minimize SF6, such as carbon dioxide (CO2) and air. This paper aimed to study the effects of field uniformity towards breakdown characteristic of air-CO2 gas mixtures under AC and DC voltage. Two types of electrodes were used in this experiment which are sphere-sphere electrode (D=5cm) and the rod-rod electrode. Other than that, there are five level of gap distances (0.5cm-2.5cm) with three mixing ratios (100% air–0% CO2, 70% air–30% CO2, 50% air-50% CO2) in 2 bar (abs). The results show the breakdown voltage (U50) of the sphere-sphere electrode is higher than the rod-rod electrode under AC and DC voltage. Besides, as the U50 goes higher, the Emax will be decreasing in any mixing ratio under AC and DC voltage. As for the results, the sphere-sphere electrode is more uniform field than the rod-rod electrode. Moreover, the sphere-sphere electrode has shown the highest withstand capacity of breakdown since they have provided less stress to the field gaps.